Assessment of Pattern of Disability Certificates Issued In a Government Tertiary Care Hospital of Karnataka South India -A Three Year Study - Thejeshwari H Lingappa; Poornima B Khot; Siddharam S Metri; Sundar Muniswamy (Medsci Publications, 2019)
Background: To facilitate the national objective under the Rights of Persons with Disabilities Act, 2016 (RPWD) it is essential to collect, compilate and analyse the data on disability at each level of health care and identify the constraints with same. The study conducted to assess the type of Disability certificates issued in tertiary care hospital; to identify the socio-demographic factors among Disability certificate beneficiaries; and to determine the degree of disability among Disability certificate beneficiaries.  Methodology: A cross-sectional study of on all type disability certificates issued as per (IDEAS) at a tertiary care hospital for three year period was done using a predesigned proform; disability certificates with complete details alone were included in the study ,data was analysed by SPSS 16 Results: 2437 certificates were issued .majority by 25.2% orthopaedics, 1.97 male: female disabled gender ratio. 30.4% disabled belong to vulnerable age group. 59% from rural locality, moderate degree disability commonest. Gender &locality and gender &degree of disability statistically significant (p<0.05) Conclusions: there is an increasing trend in utilization of disability certificates at district hospital. Marginalization of disabled woman needs further exploration.